Time in time : short poems, long poems, and the rhetoric of North American avant-gardism, 1963-2008 (McGill-Queens University Press, 2013)
Edgar Allan Poe, arguing that brevity and intensity were the essence of poetry, declared there was no such thing as a long poem. It can also be said there is no difference between a short and a long poem except duration: a measure of time. Time in Time examines what the difference really is, and investigates the interplay of short and long forms in contemporary poetry. Moving beyond the opposition of lyric and experimental schools, Time in Time constructs a history of recent North American efforts to bring about a more open poetic form. Contributors explore ways in which the work of Louis Zukofsky, William Carlos Williams, Jackson Mac Low, George Oppen, Hannah Weiner, A.R. Ammons, Marjorie Perloff, Erín Moure, Ron Silliman, and Kenneth Goldsmith reconceives, reframes, and sometimes interknits the possibilities of short and long poems. In doing so, the collection offers insight into the affiliative networks and inter-generational lines of avant-gardism on the continent. Attuned to the surprising reversals and unstable categories of the period, Time in Time illuminates the ongoing encounter of literary creativity with the limits and possibilities of form. Contributors include Adam Dickinson (Brock University), Kerry Doyle (York University), Rachel Blau DuPlessis (Temple University), Steve McCaffery (SUNY Buffalo), Erín Moure (Montreal), Michael O'Driscoll (University of Alberta) Jennifer Russo (City University of New York Graduate Center), and J. Mark Smith (Grant MacEwan University).